Pengaruh Penerapan Metode Pembelajaran Simulasi Jual Beli terhadap Pemahaman Konsep Pengurangan Bersusun Kelas III MI Ma’arif Al-Hasani - Afrohul Himmah Arvina; Arissona Dia Indah Sari; Arya Setya Nugroho (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to determine the initial ability and influence of the application of the buying and selling simulation learning method on the ability to understand the concept of class III stacked reduction at MI Ma'arif Al-Hasani. The method used in this study is a quantitative method with a type of research, namely pre-experimental design. Data collection in this study uses tests, namely pre-test to determine students' initial ability and post-test to determine the effect of the application of the buying and selling simulation learning method on students' understanding of concepts. The data analysis used was descriptive statistical analysis and inferential analysis. The population in this study is all third grade students of MI Ma'arif Al-Hasani for the 2024/2025 school year. The results showed that students' concept comprehension ability increased with an average pre-test score of 52.70 and an average post-test score of 89.22. This is also in accordance with Asymp's values. Sig. 2 (tailed) of 0.000 < 0.05, it can be concluded that "Hypothesis Accepted" so that there is an effect of the application of the buying and selling simulation learning method on the understanding of the concept of layered reduction in class III MI Ma'arif Al-Hasani.